TIBAQ DALAM AL-QUR'AN - Nazua Amelia Putri; Suci Rahmadani (Wahdatul Ulum Institute, 2026)
This study examines the use of tibaq (al-ṯibāq) as one of the prominent rhetorical devices in the Holy Qur’an. Tibaq is a figure of contrast that brings together two words or expressions with opposing meanings within a single sentence, whether in terms of wording or meaning. This study aims to identify patterns of tibaq, classify its types, and analyze its rhetorical functions and theological implications within the Qur’anic text. The method employed is qualitative textual analysis based on the classical balaghah approach, drawing upon the works of earlier scholars who specifically addressed the science of badi’ and Arabic stylistics. The research findings indicate that tibaq in the Qur’an does not merely serve as a literary ornament but plays a strategic role in conveying the majesty of Allah’s attributes, depicting the duality of the universe, and reinforcing the theological arguments underpinning Islamic teachings. It was also found that tibaq in the Qur’an appears in two main forms: tibaq al-ijab, which directly juxtaposes two opposing terms, and tibaq al-salab, which creates contrast through negative constructions. The widespread use of tibaq in verses dealing with the natural world and eschatology indicates that semantic contrast is a deliberate and planned rhetorical device designed to evoke awareness, reflection, and faith in the reader. This study is expected to contribute to a deeper understanding of the beauty of the Qur’an’s style and to enrich the discourse on i’jaz al-bayan in contemporary Qur’anic studies.